2012
DOI: 10.1038/ncb2622
|View full text |Cite|
|
Sign up to set email alerts
|

MCUR1 is an essential component of mitochondrial Ca2+ uptake that regulates cellular metabolism

Abstract: Ca2+ flux across the mitochondrial inner membrane regulates bioenergetics, cytoplasmic Ca2+ signals and activation of cell death pathways1–11. Mitochondrial Ca2+ uptake occurs at regions of close apposition with intracellular Ca2+ release sites 12–14, driven by the inner membrane voltage generated by oxidative phosphorylation and mediated by a Ca2+ selective ion channel (MiCa15) called the uniporter16–18 whose complete molecular identity remains unknown. Mitochondrial calcium uniporter (MCU) was recently ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
391
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 452 publications
(423 citation statements)
references
References 35 publications
20
391
1
4
Order By: Relevance
“…5 We found that inhibition of mitochondrial Ca 2C uptake by knockdown of MCU or MCUR1 recapitulates the bioenergetic features observed after InsP 3 R inhibition, namely a decrease in ATP levels, AMPK activation, and induction of prosurvival autophagy ( Fig. 1), 6,7 thus confirming the essential role of Ca 2C communication between the ER and the mitochondria for cellular homeostasis.…”
Section: Casupporting
confidence: 62%
“…5 We found that inhibition of mitochondrial Ca 2C uptake by knockdown of MCU or MCUR1 recapitulates the bioenergetic features observed after InsP 3 R inhibition, namely a decrease in ATP levels, AMPK activation, and induction of prosurvival autophagy ( Fig. 1), 6,7 thus confirming the essential role of Ca 2C communication between the ER and the mitochondria for cellular homeostasis.…”
Section: Casupporting
confidence: 62%
“…MCU constitutes the pore-forming subunit (Baughman et al, 2011; De Stefani et al, 2011), and interacts with several proteins to regulate its activity, including Mitochondrial Calcium Uptake protein 1 (MICU1) (Perocchi et al, 2010), its paralogs MICU2 and MICU3 (Plovanich et al, 2013), Mitochondrial Calcium Uniporter Regulator 1 (MCUR1) (Mallilankaraman et al, 2012), and Essential MCU Regulator (EMRE) (Sancak et al, 2013). EMRE is a membrane protein that interacts with and is essential for MCU-channel activity in mammalian cells (Sancak et al, 2013) and may tether MICU1 to the channel complex (Tsai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…MICU1 was originally proposed to be necessary for MCU-channel activity (Perocchi et al, 2010). Subsequent studies suggested that it instead plays a critical role in inhibiting MCU activity in the low-[Ca 2+ ] c regime, a mechanism referred to as “gatekeeping”, that imposed a [Ca 2+ ] c threshold for channel activation at ~1–3 μM (Mallilankaraman et al, 2012; Csordás et al, 2013; Patron et al, 2014). Other studies suggested that MICU1 is necessary to promote mitochondrial Ca 2+ uptake in response to [Ca 2+ ] c elevations (Perocchi et al, 2010; Csordás et al, 2013; Patron et al, 2014; Kamer and Mootha, 2014; Antony et al, 2016), with some suggesting that it plays dual roles in gatekeeping and cooperative channel-activation (Csordás et al, 2013; Antony et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The recent identification of several protein families making up the mitochondrial Ca 2+ uniporter complex (MCUC) in mammals, including the pore-forming MCU (MCU and MCUb;Baughman et al, 2011;De Stefani et al, 2011;Raffaello et al, 2013), and the regulatory, associated MICUs (MICU1, 2, and 3; Perocchi et al, 2010;Plovanich et al, 2013), EMRE (Sancak et al, 2013), and MCUR1/CCDC90A (although potentially not directly; Mallilankaraman et al, 2012b;Paupe et al, 2015), has spurred intense research across the biomedical disciplines Mallilankaraman et al, 2012a;Csordás et al, 2013;Hoffman et al, 2013;Marchi et al, 2013;Pan et al, 2013;Raffaello et al, 2013;Kovács-Bogdán et al, 2014;Logan et al, 2014;Patron et al, 2014;Wang et al, 2014). While some genes of the complex components appear not to be present in plants (e.g., MCUb and EMRE), others have multiple homologs (six for the functional poreforming subunit MCU in Arabidopsis [Stael et al, 2012] and maize [Zea mays; Meng et al, 2015] and two for MCUR1/CCDC90A in Arabidopsis), suggesting potential functional modification and/or differentiation.…”
Section: Introductionmentioning
confidence: 99%